2016
DOI: 10.1111/risa.12545
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Impact and Implementation of Disaster Education: Programs for Children Through Theory‐Based Evaluation

Abstract: A main weakness in the evaluation of disaster education programs for children is evaluators' propensity to judge program effectiveness based on changes in children's knowledge. Few studies have articulated an explicit program theory of how children's education would achieve desired outcomes and impacts related to disaster risk reduction in households and communities. This article describes the advantages of constructing program theory models for the purpose of evaluating disaster education programs for childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 33 publications
0
22
0
4
Order By: Relevance
“…For response professionals, household preparedness measures should be presented as small, easily achievable steps that will benefit their family and help them better perform their response duties. Further research could also explore the opportunities that enhanced school-based hazard education and its links to community-based public education offer as a way to increase community empowerment and participation in preparedness activities (Johnson et al 2016;Ronan et al 2016).…”
Section: Additional Theoretical and Practical Implicationsmentioning
confidence: 99%
“…For response professionals, household preparedness measures should be presented as small, easily achievable steps that will benefit their family and help them better perform their response duties. Further research could also explore the opportunities that enhanced school-based hazard education and its links to community-based public education offer as a way to increase community empowerment and participation in preparedness activities (Johnson et al 2016;Ronan et al 2016).…”
Section: Additional Theoretical and Practical Implicationsmentioning
confidence: 99%
“…This research uses the research method of development [9], its phases are: preliminary study, collecting information and literature study, product design, design validation, design improvement, model testing, model revision and wider testing. This article is only limited to the product design.…”
Section: Methodsmentioning
confidence: 99%
“…Other research related to the development and application of disaster mitigation learning in children or at the school level has been carried out in several countries, for example in New Ireland, Bangladesh, Cuba and China [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Smyth (1996) suggested that the training campaigns and programs initiated for improving the information, skills, and behaviors necessary to solve environmental issues should be arranged sustainably according to target groups. Some studies demonstrate that effective training provided to students also helps to increase the DRR awareness of their families (Johnson, Ronan, Johnston, & Peace, 2016;Lidstone, Stoltman, & DeChano, 2004;Ronan et al, 2015;Ronan et al, 2008).…”
mentioning
confidence: 99%
“…Furthermore, the content of the units related to disasters at primary and secondary levels (age 6-14) generally consisted of preparation and protection against disasters, while the disaster content of those at high-school level (age 15-17) was related to detailed information about the causes of disasters, civil protection, mitigation and response activities (UNICEF & UNISDR, 2011). On the other hand, it appears that the majority of the previous studies on disasters and disaster education in Turkey focused on earthquakes (for example, Aydin & Coskun, 2010;Gulay, 2010;Kirikkaya, Çakin, Imali, & Bozkurt, 2011;Öcal & Topkaya, 2011;Oral, Yenel, Oral, Aydin, & Tuncay, 2013). The literature review of Değirmençay and Cin (2016) reported that the majority of these studies were quantitative studies focused on keywords or titles such as disaster protective behavior, disaster knowledge, hazard perception, metaphoric studies on disasters, methods used in teaching disaster subjects, disaster curriculum, and emergency management.…”
mentioning
confidence: 99%